ANALISIS BALANCED SCORECARD PENGELOLAAN KEARSIPAN REKAM MEDIS ELEKTRONIK DI RSUD KOTA YOGYAKARTA - Nuratia Rahma; Basuki, Basuki; Eny Sulistyowati (Yayasan Nusantara Hasana Berdikari, 2025)
Digital transformation in hospital information systems demands a more effective, efficient, and secure management of medical record archives. This study aims to analyze the performance of electronic medical record (EMR) archiving management at RSUD Kota Yogyakarta using the Balanced Scorecard (BSC) approach. The study adopts a qualitative descriptive method based on secondary data derived from the 2024 performance report (LKIP), financial statements (CaLK), and strategic planning documents. The analysis reveals that from the financial perspective, the hospital demonstrates budget efficiency with a revenue realization of 116.29%. However, from the customer perspective, a decrease of 0.76 points in the Public Satisfaction Index (IKM) occurred despite the implementation of digital innovations. The internal business process perspective shows good performance indicator achievements, yet lacks documented SOPs for EMR management and data protection policies. From the learning and growth perspective, staff training is unstructured, and digital competence is not yet clearly mapped. The study recommends strategic improvements in SOP development, staff capacity building, and digital literacy enhancement to ensure the successful transformation of the hospital’s archiving system.